Systematic Comparison of Different Meta-analyses, Systematic Reviews and HTA Reports on Cervical Cancer Screening based on Cytology or HPV Test - Jentschke, M.; Hillemanns, P. (Geburtshilfe und Frauenheilkunde, 2016)
Introduction: Cervical cancer screening programs all over the world are being radically revised; preventive screening is increasingly based on detecting infection with human papillomavirus (HPV). This change was driven by large international studies (comparing cytological and HPV-based screening), which were then summarized in systematic reviews or HTA reports. We carried out a systematic comparison of these meta-analyses, comparing their contents, quality, results and recommendations. Material and Methods: A systematic search in MEDLINE identified eight meta-analyses. Seven more papers were also included in our analysis. The quality of these publications was reviewed using the AMSTAR criteria and presented in tabular form. Results: There were significant differences with regard to the primary studies included in the meta-analyses, the quality of the meta-analyses, the endpoints, and the outcomes and recommendations based on these endpoints. Conclusion: Different meta-analyses on the same or similar issues sometimes came to quite different conclusions because they used different approaches. This is quite significant because the underlying primary data did not change. The data indicated that HPV-based screening was superior. The heterogeneity of the meta-analyses affects the decisions taken by policymakers in the healthcare system.
Keywords: cervical cancer screening; HPV; cytology; dysplasia